The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.14746/ssllt.2018.8.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Revising the Metacognitive Awareness of Reading Strategies Inventory (MARSI) and testing for factorial invariance

Abstract: In this study, we revised the Metacognitive Awareness of Reading Strategies Inventory (MARSI), a self-report instrument designed to assess students' awareness of reading strategies when reading school-related materials. We collected evidence of structural, generalizability, and external aspects of validity for the revised inventory (MARSI-R). We first conducted a confirmatory factor analysis of the MARSI instrument, which resulted in the reduction of the number of strategy statements from 30 to 15. We then tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(120 citation statements)
references
References 21 publications
5
91
0
9
Order By: Relevance
“…The instrument to collect data used in this research was a questionnaire. It was adopted from MARSI (Metacognitive Awareness of Reading Strategies Inventory) especially the one revised (MARSI-R) by Mokhtari et al (2018). MARSI-R consists of 15 items that describe the strategies or actions use when reading academic or schoolrelated materials such as book chapters, journal articles, and stories.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The instrument to collect data used in this research was a questionnaire. It was adopted from MARSI (Metacognitive Awareness of Reading Strategies Inventory) especially the one revised (MARSI-R) by Mokhtari et al (2018). MARSI-R consists of 15 items that describe the strategies or actions use when reading academic or schoolrelated materials such as book chapters, journal articles, and stories.…”
Section: Methodsmentioning
confidence: 99%
“…The strategies on the MARSI-R inventory were scored on 1-5 scales. According to Mokhtari et al (2018), the scores obtained provide three types of information such as individual score, scale score, and composite score. An individual score for each reading strategy reveals which strategy the students are aware of and use or may not aware of or use.…”
Section: Methodsmentioning
confidence: 99%
“…First, we tested the configural invariance by conducting CFA separately for each group (boys and girls) as suggested by Dimitrov (2010). Obtaining configural invariance refers to invariance of the model configuration across boys and girls (Mokhtari et al, 2008). Good fit indices were obtained for both genders: TLI > 0.90 and SRMR < 0.06 (Hu and Bentler, 1999;Schermelleh-Engel et al, 2003).…”
Section: Measurement Invariance Analysis By Gendermentioning
confidence: 99%
“…The study confirmed the higher level of reliability and validity of Chinese version of MARSI. Mokhtari, Dimitrov and Reichard (2018) confirmed that the first version of MARSI has been translated into several languages, such as Arabic, Chinese, Czech, Persian, French, German, Greek, Indonesian, Japanese, Korean, Polish, Slovenian and Spanish to test MARS. The MARSI has been used in many published master's or doctoral dissertations and in refereed journals articles.…”
Section: Sheikh Soomro and Hussainmentioning
confidence: 52%